PENERAPAN PEMBELAJARAN KONTEKSTUAL DALAM MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATERI VOLUME BALOK DI KELAS V SD NEGERI 54 BANDA ACEH - Nasruddin . (Universitas Syiah Kuala, 2015)
This research is a classroom action research that discusses the application of contextual learning in improving students’ chievement in beam volume to 5 grade students at SDN 54 Banda Aceh. The problems were a major focus of this research is How the students’ activity, teacher’s acticity and student learning outcomes by using contextual approach to the material volume of the beam in class V SDN 54 in Banda Aceh? This study aims to determine the activity of the student, the teacher activity and student learning outcomes by uisng contextual approach to the material beams volume in class V SDN 54 in Banda Aceh. The approach used is qualitative and data analysis using percentages. Results showed activity of students has increased from the first cycle to the third cycle. It can be seen from the average score obtained in the first cycle of 3.25 (65%) in the second cycle by 3.63 (72.60%) and the third cycle of 4.38 (87.60%). The activities of teachers in the first cycle to obtain a value of 4.32 (86.40%), the second cycle by 4.63 (92.60%) and the third cycle of 4.7 (94%). Activity of students in Cycle I get the value of the average grade of 66.30 and students who completed following the learning process as many as 17 students (62.96%) of 27 students. In the second cycle, the value of the average grade achieved by the students at 71.85 and students who completed following the learning process as many as 21 students (77.78%) of the 27 students who take the learning process. While the third cycle the average value obtained by the students at 79.26 and 26 students completed (96.29%) in participating in the learning process of beams volume. Learning Outcomes students increased due to the use of contextual approach.Keywords: Contextual Approach, Beams Volume